Depression of the Cities: Key to Healing - Lidin, Konstantin (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The problem of search of an authenticity of the cities looks very actual and draws attention of numerous researchers. In the article the analogy between the human person and the city in this problem is used. For the person, as well as for the city, awareness of own identity is necessary to resist depressive tendencies. It is shown that symptoms of depression of the person are similar to the ones for depression of the cities. The identity of the city necessary for opposition of a depression is offered to be looked for in two planes - historical and geographical (to be looked for in historical and geographical plane). The historical plane is made by local myths and legends of the city and its inhabitants. The geographical plane of identity is concentrated on features of relief, climate, flora and fauna of that region in which the city is located.